(untitled) (Al-Academy, 2024)
The visual attraction of the fundamentals that require the availability in the design business, to achieve the needs of different social interactive and the need for recreation or entertainment as well as financial need and as such has considered the importance of a researcher studying the mechanics of visual attractions in the interior spaces have been identified according to the research problem the following question:What are the mechanisms of visual attractions in the interior spaces and the current research aims to Recruitment mechanisms of visual attractions in the design of interior spaces as determined by three research limits are:• Reduce the objective: the mechanics of visual attraction.• Reducing the spatial: Shops selling baby clothes to Rusafa.• Reduce temporal: 2010-2012 .It was known researcher of terms related to the subject matter, namely: (mechanics, visual attraction)The second chapter covered the theoretical framework has included three main themes, namely:1. Stimuli affecting the visual attraction.2. Design considerations of space through the internal structural elements and aesthetics of interior space design.3. Relations of the design space of procedure.The third chapter dealt with research procedures and results and conclusions of the researcher remember some of them:1. Poor design or construction of the idea led to the lack of visual attraction. Through the selection of people who are not with specialization or experience, which has lost a lot of internal space design featured on the impact of the recipient.2. There are a lot of the absence of sensory effects and formal, which draws our attention because of their characteristics affecting the visual perception of the visual attraction exception of the sample (1).3. Weak ties design in terms of the presence of power optical affecting them and the adoption of a recipe simplicity and abstraction in structural elements of the space of the internal led to the weakness of excitement in the structure design, as it can be achieved by the excitement through the mechanics of unity, balance and rhythm and contrast, contrast, harmony and compatibility with leading this diversity to enrich the inner space .Then came the recommendations and proposals as follows: 1. To achieve the optical centers attract the researcher recommends the construction of a structural system in harmony with the aesthetics of interior design products bred visible formal compliant.3. Emphasis on activating the role of design relations, especially relations with influential formal symbolic and expressive and functional visual stimulus to attract.Research suggestions: 1. Study of the techniques of contemporary technology and employment in line with the nature of space.2. Study on the basis of visual attraction links axes of movement and how to pull it.